URBANISASI DAN PENGEMBANGAN KOTA DI INDONESIA - Prijono Tjiptoherijanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
Urbanization is not simply the phenomenon of a population problem, but is also a political, social, cultural, and economic phenomena. Study of urbanization patterns is important due to abundance reports which point out that rapid expansion of the population growth rate, living in big cities has increased enormously. The problems associated with exaggerated growth may create a primary city, that in its excessive process will have negative and disadvantage impacts for the development and the well-being of such a city.The omnipresent growth of slums, the underprivileged areas in the center and the outskirts of a city has provided a robust evidence that the proper plans at the heart of this, is paramount importance to the city development with regard to its inhabitants. Effective solutions to urbanization problems and to establish a relevant city development are to utilize effeciency in people empowerment as well as the equitable distribution of the public welfare, not just cosmetic and artificiality of the city development plan.